Family Law Cases as Law Reform Litigation: Unrecognized Parents and the Story of Alison D. v. Virginia M. - Goldberg, Suzanne B. (Columbia Journal of Gender and Law, 2008)
Although the gap between law and lived experience comes as no surprise to most people, the divergence is especially striking-and disturbing-in the area of family law. Legal training quickly reveals that love is not a foundational element of family law, yet it can still be jarring to find that love has little, if any, bearing on the contours of the legal family. Love, after all, does not account for who can and cannot marry. Nor does the past love of an unmarried couple trigger the protections of divorce should the couple separate. When children are involved, we might be especially inclined to think that love should carry some weight in determining whether a parent- child relationship will be recognized. Yet even here, again, love is often not relevant to the analysis. While an adult might feel like a parent, be treated like a parent, and be “Mom” or “Dad” to the child, in many states that adult will not actually be a parent within the law, absent adoption or biological parentage. For families in those states, a non-legal parent may have no legal recourse if a couple separates and the “legal” parent bars him or her from seeing the child. As a matter of law, the non-legal parent and child in this situation are no closer than strangers.